Notary Deed Security Application Using RC4 Method on Android-Based - Reza Saputra; Yuli Asriningtias (Lembaga Pengembangan Kinerja Dosen, 2023)
In the digital era, security concerns related to notary deeds can arise due to several factors, particularly in safeguarding important documents. Without a secure application, these important documents, such as notary deeds, can be threatened by unauthorized access. This could result in material or reputational loss for both the notary and the client. This application provides facilities for users to encrypt and decrypt notarial deeds in several file types, including PDF, Excel, Microsoft Word, and images. The encryption and decryption process in this application utilize the RC4 method. In this application, users can process notarial deeds to be encrypted according to the type of document file they possess in order to obtain an encrypted files ready to be sent or exchanged notary deed data. The application result will display the history of the encrypted document, the date when the file was encrypted, as well as the token in the file for the decryption process. Keywords: Notarial Deed, RC4, Encryption, Decryption, Token